The Authority of Notary Supervisors in Taking Action Against Violations of The Dissemination of Deed of Agreement on Social Media - Wulandari, Irvi Wuri; Dewi, Anak Agung Istri Ari Atu (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to find out clear arrangements related to the authority of the regional supervisory assembly as the guardian of notary honor to monitor and respond to the attitude of notaries, especially in taking action against notary violations of the dissemination of deeds of agreement on social media. The formulation of the problem in this study is first, how is the responsibility of notaries who disseminate deeds of agreement through social media, and second, how is the authority of notary supervisors in taking action against these violations. In this writing, the researcher uses a normative research method with a statutory approach and conceptual approach. Based on the research conducted by the researcher, the conclusions are obtained, namely: First, notaries who disseminate deeds through social media can be held accountable ethically, civilly and criminally. The liability is certainly based on the fulfillment of the elements of the act committed, whether the act meets the elements of violation of the code of ethics, or meets the elements of the offense for criminal liability, and whether the act meets the elements of unlawful acts for civil liability. Second, the Notary Supervisory Council has a mechanism for enforcing ethics and imposing administrative sanctions. The sanctions are imposed if the notary who disseminated the deed on social media is proven to have violated the code of ethics based on the Supervisory Panel's examination. Ethical sanctions can be in the form of: a). verbal warning; b). written warning; c). temporary dismissal; d). proposal for honorable dismissal; or e). proposal for dishonorable dismissal. In the process of examining a notary who commits an ethical violation, the principle of presumption of innocence must be put forward until the decision of the Supervisory Panel states that the person concerned is proven guilty.